Misaligned anisotropies in spin-valve films studied through magnetoresistance and magnetization measurements. (12th April 2019) - Limeira, V P C; Nagamine, L C C M; Geshev, J; Cornejo, D R; Garanhani, F J
Abstract: Magnetization and magnetoresistance properties of Py/Cu/Py/IrMn spin valve (SV) films are studied in the framework of the modified antiferromagnetic domain-wall model applied to a granular multidomain system. In the simulations, a misalignment between the in-plane easy magnetization axes of the Py and IrMn is considered. Magnetization and magnetoresistance data are simulated for a number of field orientations and a fairly good agreement with the experiment is found. The same holds for the respective distributions of the coercive and exchange-bias field values determined from magnetoresistance first-order reversal curves (MR-FORC) obtained for magnetic field parallel to the direction of that applied during the sample deposition. Both experimental and theoretical data of the angular variations of the magnetoresistance at constant fields are successfully used to obtain the misalignment angles. For some samples, mostly those with thinner Py layer coupled to IrMn one, our results indicate that the misalignment is due to interfacial magnetic frustration. Moreover, it is shown that MR-FORC diagrams are useful to extract information about the alignment of the grains along the field-cooling directions in SVs, as well as that these can be used to determine the threshold of the continuity of the pinned magnetic layer.